(3GdhGajI TQM GdcGajI GdTGajIs - (3eMeO Hf YHO Gddg, GHf eGdc GdWGFj GdLqjGfj, CHh YHO Gddg, LeGd GdOjf,J (B672 (3g` s ((3OeTb s)
(3ChdgG (B:s
(3bGd GdTjN Hf eGdc SCdfi HYV GdCdHGA GdeYJfjf HMbGFb GdCfHGA Cf CJdh GdcGajI GdTGajI HTQM JNa Hg Gdehfg s
(3BNQgG (B:s
(3hgh HjJ UZjQ ai UOQ GdUdU GdcKjQ hQhi hbO LYdJ fXe gPG GdHGH ecedkG CHhGH PG GdcJGH aGdMeO ddg Ydi JcejdI Je GdcJGH HMeO Gddg hYhfg hMSf Jhajbg s
(3HgG fXGe GdJYbjHIs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B223 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B130s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1998s
Keywords: (3GdfMhs